1977
DOI: 10.1029/gl004i002p00091
|View full text |Cite
|
Sign up to set email alerts
|

Steady‐state seismic slip – A precise recurrence model

Abstract: Regularity of seismic slip along a 9 km segment of the Calaveras fault zone is believed to result from steady‐state loading of a creeping fault to generate stresses on an isolated stuck patch which moves in a stick‐slip event in the magnitude range 3 to 4 whenever a critical threshold is reached. The patch behavior can be described by a simple model similar to the spring‐driven frictional models used in laboratory simulations of stick‐slip. The (M ≥ 3) recurrence time for this model is directly proportional to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
50
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(53 citation statements)
references
References 12 publications
2
50
0
1
Order By: Relevance
“…Although most of the earthquake generation models currently used for seismic hazard evaluation assume a Poisson (Cornell 1968;Caputo 1974;Shah and Movassate 1975) or other memory-less distributions, studies in the last few decades have concluded that the large earthquakes in many regions are temporally dependent (Bufe et al 1977;Sykes and Quittmeyer 1981;Papazachos 1989;Stein et al 1997;Parsons et al 2000). Two kinds of time-dependent models have been suggested: the slip-predictable model and timepredictable model.…”
Section: Introductionmentioning
confidence: 98%
“…Although most of the earthquake generation models currently used for seismic hazard evaluation assume a Poisson (Cornell 1968;Caputo 1974;Shah and Movassate 1975) or other memory-less distributions, studies in the last few decades have concluded that the large earthquakes in many regions are temporally dependent (Bufe et al 1977;Sykes and Quittmeyer 1981;Papazachos 1989;Stein et al 1997;Parsons et al 2000). Two kinds of time-dependent models have been suggested: the slip-predictable model and timepredictable model.…”
Section: Introductionmentioning
confidence: 98%
“…These models are based on the fact that the time of occurrence and the magnitude of an earthquake in a region are independent of the time and magnitude of the previous and subsequent earthquakes. The independence behaviour has been observed in some seismic sequences in some regions (Gardner and Knopoff 1974) but the temporal dependence in earthquakes is observed in several regions of the world (Bufe et al 1977;Sykes and Quittmeyer 1981;Papazachos 1989;Papadimitriou and Papazachos 1994). There are two types of models concerning the relationship between the slip amount of an earthquake and time of occurrence of a large earthquake, namely, slip-predictable model and time-predictable model (Bufe et al 1977;Shimazaki and Nakata 1980).…”
Section: Introductionmentioning
confidence: 95%
“…Thus, the larger the last earthquake is, the longer is the time to the next earthquake (Shimazaki and Nakata 1980). A number of evidences are present for time-predictable recurrence model for large earthquakes along plate boundaries (Bufe et al 1977;Shimazaki and Nakata 1980;Sykes and Quittmeyer 1981). Bufe et al (1977) proposed a model of seismic slip and recurrence intervals for a segment of a fault in northern California and observed that the time interval is proportional to the amount of displacement in the preceding earthquake.…”
Section: Introductionmentioning
confidence: 97%
“…The time-predictable model appears to have been successful in predicting the timing of one event on the Calaveras fault, California (BUFE et al, 1977Valparaiso, Chile, earthquake (NISHENKO, 1985. This model also formed the basis of the Parkfield, California, earthquake prediction experiment (BAKUN and LINDH, 1985;BAKUN and MCEVILLY, 1984).…”
Section: Introductionmentioning
confidence: 99%